Respons Mahasiswa terhadap Kebijakan Deradikalisasi Pemerintah - Della Putri Apriliana; Ayu Irmasari Raharjanti; Ayu Sulastri; Dinar Noviana; Nindia Nur Baity Suwarno (Universitas Islam Negeri Raden Mas Said Surakarta, 2017)
This study aims to know the student of IAIN Surakartaâ€™s responds to the effective policy of deradicalization conducted by the government to reduce radicalism and terrorism. Based on the qualitative method the study revealed that seminar/public lecture becomes the key program to prevent radicalism, but it much needed the synergy work between government and students. Even though, the activities of deradicalization have not effectively done, since its implementation still partial and temporal. There is no clear and good synergy movement, between government and society.Â Keywords:Radicalism, Deradicalization, Student responseÂ